Dental findings of a child with Wolf–Hirschhorn syndrome - N. J. JOHNSTON & D. L. FRANKLIN (Paediatric Dentistry, 2006)
In 1965, Wolf et al . [1] and Hirschhorn et al . [2] first reported a syndrome associated with the deletion of the short arm of chromosome 4.